(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we introduce a new class of Frobenius-Tangent polynomials, derived from the Bell numbers and Apostol-type functions. We conduct a detailed investigation into the properties of these polynomials, utilizing various analytical techniques. By employing generating functions for Bell-based Apostol-Frobenius-Type Tangent polynomials of higher order, we obtain both explicit and implicit summation formulas and its relation to Appell polynomials.